Design and experimental verification of flexible plate-type piezoelectric vibrator for energy harvesting system - Park, Jeong-Hyun; Lim, Tae-Woo; Kim, Sung-Dae; Park, Sang-Hu (International Journal of Precision Engineering and Manufacturing-Green Technology, 3(3), 2016)
Piezoelectric systems are commonly utilized to transform mechanical vibrations to electrical energy that can be used to diverse power devices. In this work, it has been studied to improve the efficiency of a piezoelectric system with modification of the shape of a piezoelectric module and its vibration mode using analysis and experimental approaches. The basic shape of piezoelectric plate used in this work is width of 10 mm, length of 30 mm, and thickness of 0.2 mm. The structural design of a piezoelectric module is optimized to increase an electrical energy generation using a Taguchi factorial effect analysis method. The maximum terminal voltage was defined as a characteristic value to evaluate the optimal design parameters. Through this work, we have selected an optimal one among three designed different types of piezoelectric modules. And the optimal module shows that the output power was approximately 10 to 30% higher than other modules.